LB02.05: CONTROLLING AND LOWERING BLOOD PRESSURE WITH THE MOBIUSHD DEVICE. (June 2015) - Spiering, W.; Van Der Heyden, J.; Devireddy, C.; Foster, M.T.; Bates, M.C.; Kroon, A.A.
Abstract : Objective: This is a multi-center (6 centers) non-randomized, first-in-man assessment of a nitinol self-expanding rectangular cuboid implant (MobiusHD) designed to increase carotid sinus arterial wall strain without impacting pulsatility or laminar flow. The geometric changes of the carotid sinus enhance baroreceptor sensitivity thus decreasing sympathetic activity and lowering BP. Patients with stage 2 resistant hypertension (3 or more antihypertensives, of which one is a diuretic, and office SBP 160 mmHg or higher), without obstructive carotid disease received a unilateral carotid sinus MobiusHD implant. Incidence of serious adverse events and unanticipated adverse device effects were collected along with changes in blood pressure (BP) measured during 1-year follow-up. Design and method: This is a multi-center (6 centers) non-randomized, first-in-man assessment of a nitinol self-expanding rectangular cuboid implant (MobiusHD) designed to increase carotid sinus arterial wall strain without impacting pulsatility or laminar flow. The geometric changes of the carotid sinus enhance baroreceptor sensitivity thus decreasing sympathetic activity and lowering BP. Patients with stage 2 resistant hypertension (3 or more antihypertensives, of which one is a diuretic, and office SBP 160 mmHg or higher), without obstructive carotid disease received a unilateral carotid sinus MobiusHD implant. Incidence of serious adverse events and unanticipated adverse device effects were collected along with changes in blood pressure (BP) measured during 1-year follow-up. Results: So far 15 patients, mean age 55 (39–76) years, of the anticipated 40 patients received a MobiusHD implant. Mean pretreatment office BP was 181/102 (±18/11) mmHg with a median of 4.5 prescribed antihypertensives (daily defined dose (DDD): 6.6) and 6 patients had failed on renal denervation. During follow-up 3 patients had serious adverse events related to procedure or device: hypotension (n = 2) and closure device failure requiring repair (n = 1). During follow-up eleven (11) patients showed significant BP lowering (i.e. more than 10/5 mmHg decrease in office BP) and 8 required reduction in antihypertensives. Changes in DDD and BP after MobiusHD implant Figure. No caption available. Conclusions: So far, implanting the MobiusHD device in patients with stage 2 resistant hypertension seems to be safe and shows promising results in BP lowering.